The heavy mineral indicator adds a new dimension to airborne radiometrics - Hooshyari-Far, I.; Kepic, Anton; Carson, M. (2019)
© 2019 24th European Meeting of Environmental and Engineering Geophysics. All rights reserved. For many years the output of radiometric surveys are maps of total count gamma activity and estimations of K, U, Th. Our work puts the focus upon using the long neglected aspects of the radiometric spectrum: the scattered gamma ray radiation. The heavy mineral indicator (HMI) is computed form a ration of low energy versus high energy scattered gamma rays. It is in effect the ratio of Photoelectric effect versus Compton effects. The Elashgin case history demonstrates that low-level and high resolution full spectrum radiometrics provides good data for the HMI technique. HMI values are dominated by Fe concentration due the abundance of Fe over other high atomic number elements. Areas composed of higher atomic numbers, mostly due to the iron content, such as ferricretes and laterite show up clearly in the Elashgin data without the need to be “interpreted” with respect to geological context. With the high resolution of modern radiometrics on planes and future drones this technique works well for remote sensing. An exciting aspect of HMI analysis for airborne radiometrics is not just the future, but the past: many high quality full spectrum data sets already exist and may be easily reprocessed to reveal new geological insights.